Preliminary analysis of the Very Early Diagnosis of Systemic Sclerosis (VEDOSS) EUSTAR multicentre study: evidence for puffy fingers as a pivotal sign for suspicion of systemic sclerosis. Issue 12 (12th August 2013) - Minier, Tünde; Guiducci, Serena; Bellando-Randone, Silvia; Bruni, Cosimo; Lepri, Gemma; Czirják, László; Distler, Oliver; Walker, Ulrich A; Fransen, Jaap; Allanore, Yannick; Denton, Christopher; Cutolo, Maurizio; et al.
Abstract : Objectives: The EULAR (European League Against Rheumatism) Scleroderma Trials and Research Group (EUSTAR) has identified preliminary criteria for very early diagnosis of systemic sclerosis (SSc). Our aim was to assess the prevalence of each proposed diagnostic item in a large observational patient cohort with Raynaud's phenomenon (RP). Methods: Baseline data of 469 RP patients enrolled into the Very Early Diagnosis of Systemic Sclerosis (VEDOSS) cohort are presented. Results: 68% of all RP patients were antinuclear antibody (ANA) positive. ANA+ RP patients more frequently had previous or current puffy fingers (PuFi) (38.5% and 23.3%, p<0.01) and an SSc pattern on nailfold capillaroscopy (NC) (53.6% and 13.4%, p<0.001) than ANA− patients. Telangiectasia, current digital ulcers and digital pitting scars were also commoner in ANA+ RP patients. 38% of ANA+ patients presented with all three features, which should raise suspicion of very early SSc (ANA+RP+PuFi constitutes a 'red flag'). These patients more frequently exhibited an NC SSc pattern, sclerodactyly and telangiectases compared to ANA+ patients without PuFi. Almost 90% of patients with 'red flags' had anti-centromere or anti-topoisomerase I antibodies and/or an NC SSc pattern, and fulfilled the EUSTAR criteria for very early SSc. Previous or current PuFi were present in 23.3% of ANA− RP patients, eight of whom also had an NC SSc pattern. Conclusions: In addition to well-characterised predictive factors, PuFi is an important sign raising suspicion for underlying very early SSc in patients with RP. The relevance of PuFi in ANA− RP patients should be clarified.